2012
DOI: 10.1128/aem.00065-12
|View full text |Cite
|
Sign up to set email alerts
|

High Diversity and Novel Species of Pseudomonas aeruginosa Bacteriophages

Abstract: ABSTRACTThe diversity ofPseudomonas aeruginosabacteriophages was investigated using a collection of 68 phages isolated from Central Mexico. Most of the phages carried double-stranded DNA (dsDNA) genomes and were classified into 12 species. Comparison of the genomes of selected archetypal phages with extant sequences in GenBank resulted in the identification of six novel species. This finding increased the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 40 publications
1
57
0
1
Order By: Relevance
“…Unlike phages of other species (Nolan et al, 2006;Dorscht et al, 2009;Sepúlveda-Robles et al, 2012), P. acnes phages show a high genetic similarity. The phages may have evolved recently under limited selection, as no clear lineages can be found among the phages studied, suggesting that these phages may be relatively new to their hosts .…”
Section: Phage Strainsmentioning
confidence: 99%
“…Unlike phages of other species (Nolan et al, 2006;Dorscht et al, 2009;Sepúlveda-Robles et al, 2012), P. acnes phages show a high genetic similarity. The phages may have evolved recently under limited selection, as no clear lineages can be found among the phages studied, suggesting that these phages may be relatively new to their hosts .…”
Section: Phage Strainsmentioning
confidence: 99%
“…An electron microscopy examination of R. etli phages showed that they belong to the class Caudovirales (Myoviridae and Podoviridae), which has commonly been isolated from other Rhizobium species and many other bacterial species (9,49). It is known that phage morphology is not indicative of genetic relatedness; therefore, we distinguished phages in our collection on the basis of the genome sequence, categorizing them into four types.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have classified bacteriophages into species on the basis of genome sequence and structural relatedness (49,51). Although the number of phages analyzed in the current study was low, we propose that the genomic types of R. etli might correspond to phage species.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomic analysis (14) shows that 119X is similar to PaP2, a phage that was isolated in China (15). In addition, in a previous study, Sepulveda-Robles et al (16) reported the isolation of 68 virulent P. aeruginosa phages in Mexico. Only 13 of those phages were assigned to the Podoviridae family using electron microscopy.…”
mentioning
confidence: 99%
“…Only 13 of those phages were assigned to the Podoviridae family using electron microscopy. Based on infection, restriction, and DNA hybridization patterns, all of these phages were clustered in a single group, and a partial sequence of one of these phages (PaMx32) suggested that these organisms are similar to 119X (16). Interestingly, these podophages showed the broadest host range among Mexican strains, productively infecting 30% to 60% of the more than 100 clinical isolates tested (16); however, these isolates were unable to infect the type strains PAO1 and PA14.…”
mentioning
confidence: 99%